Humidified High Flow Nasal Cannula versus Nasal Continuous Positive Airway Pressure as an Initial Respiratory Support in Preterm Infants with Respiratory Distress: a Randomized, Controlled Non-Inferiority Trial - Shin, Jeonghee; Park, Kyuhee; Lee, Eun Hee; Choi, Byung Min (Journal of Korean medical science, 2017)
Heated, humidified, high-flow nasal cannula (HHFNC) is frequently used as a noninvasive respiratory support for preterm infants with respiratory distress. But there are limited studies that compares HHFNC with nasal continuous positive airway pressure (nCPAP) only as the initial treatment of respiratory distress in preterm infants immediately after birth. The aim of this study is to assess the effectiveness and safety of HHFNC compared to nCPAP for the initial treatment of preterm infants with respiratory distress. Preterm infants at between 30 and 35 weeks of gestational age were randomized to HHFNC or nCPAP when they showed respiratory distress in less than 24 hours of age postnatally. Preterm infants who needed invasive respiratory supports were excluded. Primary outcome was the incidence of treatment failure (defined as need for the intubation or mechanical ventilation). Eighty-five infants were analyzed. Sixteen of 42 infants randomized to HHFNC showed treatment failure compared to 9 of 43 infants using nCPAP (Risk difference 17.17 [-1.90-36.23]; P = 0.099). In terms of the reason for treatment failure, the frequency of hypoxia was significantly higher in the HHFNC group than in the nCPAP group (P = 0.020). There was no difference between the 2 groups in terms of respiratory and clinical outcomes and complications. Although HHFNC is safe compared to nCPAP, it is not certain that HHFNC is effective compared to nCPAP non-inferiorly as an initial respiratory support in preterm infants with respiratory distress.